1976
DOI: 10.1126/science.1251203
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Benzopyrene Hydroxylase Induction as a Monitor for Marine Petroleum Pollution

Abstract: Fish from petroleum-contaminated sites in the marine environment have elevated levels of benzopyrene hydroxylase activity in liver and gill tissue. This sublethal response appears to be a practical biological monitor for marine petroleum pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(49 citation statements)
references
References 2 publications
0
47
0
2
Order By: Relevance
“…P-450. Payne (1976) found elevated levels of hepatic aryl hydrocarbon hydroxylase (AHH) activity in fish from petroleum-contaminated sites, and suggested that AHH induction could be used as an indicator of petroleum contamination. Field observations by Kurelec et al (1977 confirmed the induction of AHH acitivity in fish from polluted areas.…”
Section: Introductionmentioning
confidence: 99%
“…P-450. Payne (1976) found elevated levels of hepatic aryl hydrocarbon hydroxylase (AHH) activity in fish from petroleum-contaminated sites, and suggested that AHH induction could be used as an indicator of petroleum contamination. Field observations by Kurelec et al (1977 confirmed the induction of AHH acitivity in fish from polluted areas.…”
Section: Introductionmentioning
confidence: 99%
“…Les premières études effectuées in situ datent des années 70 (PAYNE et PENROSE, 1975 ;PAYNE, 1976). L'induction peut être quantifiée en particulier par la mesure de l'activité monooxygénase EROD (EthoxyRésorufine-O-Dééthylase) catalysée spécifiquement par le cytochrome P450 1A.…”
Section: Mesure De L'induction De L'erodunclassified
“…It has been suggested for several years that the cytochrome P-4S0 monooxygenase system (more specifically, AHH activity) should be a convenient moni tor of environmental quality given its character istic induction response (Payne, 1976). Nevertheless the utility of this catalytic activity applied as a diagnostic tool requires cr i tical evaluation by a definition of baseline condi tions and careful consideration of confounding var iables (Stegeman, 1981).…”
Section: Monooxygenase Activities In Aquatic Speciesmentioning
confidence: 99%
“…Elevated levels of AHH in fish are attributed on the basis of kinetic evidence to environmental induction in several cases (Payne, 1976;Stegeman, 1978;Kuralec et al, 1977;. It has been suggested for several years that the cytochrome P-4S0 monooxygenase system (more specifically, AHH activity) should be a convenient moni tor of environmental quality given its character istic induction response (Payne, 1976).…”
Section: Monooxygenase Activities In Aquatic Speciesmentioning
confidence: 99%